2019
DOI: 10.1177/0269215519840406
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cryotherapy on pain and function in individuals with knee osteoarthritis: a systematic review of randomized controlled trials

Abstract: Objective: To investigate the effectiveness of cryotherapy on pain and physical function in knee osteoarthritis. Data sources: An electronic search was performed up to February 2019 on PubMed/MEDLINE, EMBASE, CINAHL, Lilacs, Cochrane, Web of Science, Ibecs, and Scielo databases with keywords knee osteoarthritis and cryotherapy. Methods: Two authors independently performed the study selection. All languages and publication dates were considered. The PEDro scale was used to assess the methodological quality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…2). Supplemental searches were performed to expand on key topics identified in the original literature search, i.e., subchondral bone pathology [1], knee sleeves [2][3][4][5][19][20][21], bone marrow lesions [22][23][24][25][26], clinical risk factors for knee OA progression [27][28][29][30][31][32][33], OA phenotypes [34], nonpharmacological treatments for OA [35][36][37][38][39][40][41][42][43], and clinical practice guidelines for OA management [44].…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Supplemental searches were performed to expand on key topics identified in the original literature search, i.e., subchondral bone pathology [1], knee sleeves [2][3][4][5][19][20][21], bone marrow lesions [22][23][24][25][26], clinical risk factors for knee OA progression [27][28][29][30][31][32][33], OA phenotypes [34], nonpharmacological treatments for OA [35][36][37][38][39][40][41][42][43], and clinical practice guidelines for OA management [44].…”
Section: Literature Searchmentioning
confidence: 99%
“…According to our proposed clinical model, cryotherapy might be expected to alleviate pain by temporarily reducing blood flow to joint tissues. A systematic review of RCTs identified insufficient primary studies to draw conclusions about the effectiveness of cryotherapy on pain and physical function on individuals with knee osteoarthritis [40]. However, a review of cryotherapy treatment after unicompartmental and total knee arthroplasty concluded that continuous circulating cold flow might be optimal for pain relief and minimization of pain medication use after knee arthroplasty [41].…”
Section: Cryotherapy and Heatmentioning
confidence: 99%
“…Since the random-effects model incorporates both within- and between-study variance, it is better suited than the fixed-effects model. The treatment effects were further classified as small (< 0.20), moderate (0.21 to 0.79), and large (> 0.80) according to Cohen’s criteria [ 36 ]. Heterogeneity was investigated using the chi square test.…”
Section: Methodsmentioning
confidence: 99%
“…The use of thermal modalities including cold and heat therapy is not backed by any evidence [11]. Patients may prefer to receive heat, cold, or contrast treatments to reduce pain and enhance physical function, according to study [12].…”
Section: Thermal Modalitiesmentioning
confidence: 99%